Unmasking endobronchial tuberculosis in a post-valve replacement patient on anti-coagulant therapy: a diagnostic challenge - Adiody, Supriya; N. S., Vishnu; Ravi, Manoj; Raj, Austin; Isaac, Binil (International Journal of Research in Medical Sciences, 2025)
Endobronchial tuberculosis (EBTB) is a rare yet challenging diagnosis due to its nonspecific symptoms, frequently normal chest radiographs, and variable sputum smear positivity. We report a case of a 56-year-old male with a history of aortic valve replacement on long-term warfarin therapy, presenting with massive hemoptysis requiring mechanical ventilation. Initially attributed to anticoagulation-induced coagulopathy, further evaluation with bronchoscopy revealed an endobronchial lesion, and bronchoalveolar lavage (BAL) confirmed Mycobacterium tuberculosis via GeneXpert. The patient was initiated on anti-tuberculosis therapy (ATT), resulting in clinical improvement and radiological improvement. This case underscores the diagnostic dilemma of EBTB in patients on long-term anticoagulant therapy, where bleeding is often attributed to coagulopathy rather than tuberculosis. Early bronchoscopy is crucial in high-risk patients, particularly in TB-endemic regions, to ensure timely diagnosis and treatment. This report highlights the importance of clinical vigilance in atypical presentations of TB.